An optimization platform for Poland's power sector considering air pollution and health effects. (December 2015) - Wyrwa, Artur
Abstract: The article demonstrates the features and applicability of the πESA platform designed for optimization of the Poland's power sector considering air pollution and health effects. πESA is comprised of: a bottom-up energy-economic model TIMES-PL, an air quality modelling system Polyphemus and a module for assessment of environmental and health impacts MAEH. It has been designed as a web application employing computational resources of the ZEUS cluster of the PL-Grid infrastructure. The results show, that the impact of carbon prices on the fuel and technological power generation structure is much stronger as compared to impact of fuel prices. Future PM emissions from the centralized power and heat generation sector do not differ much irrespective of energy scenario considered. For analysed cases, the statistical life expectancy in Poland due to long-term exposure to PM2.5 air pollution is reduced on average by approx. 183 days. That gives over 12 million years lost for all cohorts included in the analysis. Highlights: An optimization platform has been developed for the power sector in Poland. It allows for assessment of health impact of energy scenarios. Carbon prices have strong impact on fuel and technology transitions. Future PM emissions from power sector are comparable in all scenarios considered.